2020
DOI: 10.3390/brainsci10030135
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Traumatic Brain Injury in the United States: Rural-Urban Disparities and Considerations

Abstract: Introduction: Traumatic brain injury (TBI) remains a primary cause of pediatric morbidity. The improved characterization of healthcare disparities for pediatric TBI in United States (U.S.) rural communities is needed to advance care. Methods: The PubMed database was queried using keywords ((“brain/head trauma” OR “brain/head injury”) AND “rural/underserved” AND “pediatric/child”). All qualifying articles focusing on rural pediatric TBI, including the subtopics epidemiology (N = 3), intervention/healthcare cost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 32 publications
0
23
0
Order By: Relevance
“…Level of rurality might play a role in the incidence of TBI-related deaths in states with higher rates. Residents in rural areas experience a higher incidence of TBI ( 2 ) and might face barriers to accessing emergency medical care (including Level I trauma centers) ( 7 ) and specialized TBI care ( 8 ). Disparate TBI-related death rates might also result from risk differences in mechanisms of injury and implementation of state injury prevention policies.…”
Section: Discussionmentioning
confidence: 99%
“…Level of rurality might play a role in the incidence of TBI-related deaths in states with higher rates. Residents in rural areas experience a higher incidence of TBI ( 2 ) and might face barriers to accessing emergency medical care (including Level I trauma centers) ( 7 ) and specialized TBI care ( 8 ). Disparate TBI-related death rates might also result from risk differences in mechanisms of injury and implementation of state injury prevention policies.…”
Section: Discussionmentioning
confidence: 99%
“…As evidence suggests that rural communities have higher rates of TBI than urban communities, 2,3,17 it is important to ensure that providers who treat patients in these communities have the most up‐to‐date information about TBI best practices. Findings from this qualitative study provide insight into the perception and use of the CDC pediatric mTBI guideline among pediatric rural health care providers.…”
Section: Discussionmentioning
confidence: 99%
“…Unintentional injuries, including traumatic brain injury (TBI), are the leading cause of death and disability in children in the United States 1 . A recent review found that rural pediatric TBIs were more likely to have increased injury severity and often involved higher velocity injury mechanisms than others 2 . Additionally, a retrospective study of children using data collected as part of the Oregon Trauma Registry found that children living in rural areas had a TBI incidence rate about 50% greater than children living in urban areas 3 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Countries with the lowest and highest incidence are Sweden (12 cases per 100,000) and Australia (486 cases per 100,000). Higher incidence, severity, and mortality in pediatric TBI are observed in rural as opposed to urban areas [12]. Bimodal age distribution with peaks at 0-4 years and 14-18 years with male-gender preponderance in the pediatric population is observed [13].…”
Section: Epidemiologymentioning
confidence: 99%